Emotional and intuitive eating: an emerging approach to eating behaviours related to obesity. (13th February 2023) - Ayyıldız, Feride; Akbulut, Gamze; Karaçil Ermumcu, Merve Şeyda; Acar Tek, Nilüfer
Abstract: Emotional and intuitive eating are associated with obesity. In the present study, it was aimed to evaluate the relationship between intuitive eating and emotional eating behaviours in adults with anthropometric measurements of obesity-related disease risk and gender. Body weight, body mass index (BMI), waist, hip and neck circumferences were taken. Emotional Eater Questionnaire and Intuitive Eating Scale-2 were used for the assessment of eating behaviour. A total of 3742 adult individuals (56⋅8 % ( n 2125) female and ( n 1617) male) were participated voluntarily. The total score and subscales of EEQ were higher in females than males ( P < 0⋅001). The scores of the IES-2 subscales and the total score were higher in males than females ( P < 0⋅05). In metabolic risk classification according to waist and neck circumference, EEQ scale scores (except type of food) were higher in the metabolic risk group, while IES-2 (except body-food congruence in neck circumference) scores were higher in the non-risk group ( P < 0⋅05). While there was a positive correlation between EEQ and body weight, BMI, waist circumference, waist-height ratio, a negative correlation was found between age and waist-hip ratio. There was a negative correlation between IES-2 and body weight, BMI, waist-height ratio, waist-hip ratio. In addition, a negative correlation was found between IES-2 and EEQ. Intuitive eating and emotional eating differ by gender. Anthropometric measures and metabolic disease risk is associated with emotional eating and intuitive eating. Interventions to increase intuitive and decreasing emotional eating behaviour can be effective in preventing both obesity and obesity-related diseases.